Evaluation of pozzolanic Portland cement as geotechnical stabilizer of a dispersive clay. Issue 4 (21st April 2021) - Vakili, Amir Hossein; Selamat, Mohamad Razip Bin; Salimi, Mahdi; Gararei, Shahin Ghahremani
ABSTRACT: In this research, through a comprehensive geotechnical testing program, the pozzolanic Portland cement was investigated for its potential as treatment additive to the problematic Iranian dispersive clay. The dispersivity potential, plasticity index (PI), maximum dry density, compression index (Cc), rebound index (Cr), and sodium percentage (PS) of the clay samples were found decreased, while the unconfined compressive strength (UCS), optimum moisture content, and electrical conductivity (EC) were found increased, after treatment with the Portland cement. With 2% Portland cement and 7 days of curing, the erosion rate index (I) of the clay increased from less than 2 to more than 4, resulting in the delay of the formation of a piping failure. In terms of erosion resistance, the addition of 2% cement with 7 to 14 days curing time was found to be optimum. However, the mechanical strength developed significantly with increasing curing days and the highest strength was recorded at 90 days. Consequently, the study showed that the dispersivity behaviour, especially during the stabilization period, could be evaluated by analyzing the parameter values of I, PS, and EC.